2022
DOI: 10.1021/acsami.2c01453
|View full text |Cite
|
Sign up to set email alerts
|

An Antifatigue Liquid Metal Composite Electrode Ionic Polymer-Metal Composite Artificial Muscle with Excellent Electromechanical Properties

Abstract: Ionic polymer–metal composites (IPMC), one of the most popular materials in the field of artificial muscle research, have attracted much attention because of their high flexibility, low drive voltage (<10 V), high force density, large deformation, and so forth. However, the results show that the serious electrode fatigue crack and water loss of traditional IPMC greatly decrease its fatigue life and limit the practical application. In this study, we developed a novel liquid metal composite electrode. A layer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…For example, the self-healing function can be achieved by using liquid metal composites as electrodes. 58,59 Additionally, it has been reported that PVA is also a promising self-healing material, based on the principle of reversible dynamic chemical bonds. 60 Thus, the self-healing function of iEAPs could be achievable using the PVA/IL electrolyte developed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the self-healing function can be achieved by using liquid metal composites as electrodes. 58,59 Additionally, it has been reported that PVA is also a promising self-healing material, based on the principle of reversible dynamic chemical bonds. 60 Thus, the self-healing function of iEAPs could be achievable using the PVA/IL electrolyte developed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the addition of different alcohol solutions for assistance during the electroless plating process was proposed to allow the Nafion membrane to swell more efficiently during the reduction step. [ 69 , 70 ] The metal salt ions achieve a better distribution on the surfaces of the substrate in this way. The high‐quality, homogeneous nano‐dispersed Pt electrodes obtained became the structural basis for the large deformation and fast response of IPMC.…”
Section: Novel Electrodesmentioning
confidence: 99%
“…[ 33 , 44 , 69 , 111 ] The final step is the replacement of ions that can form a larger volume of hydrated cations (such as Li ions) inside the IPMC film. [ 70 ] Since the deformation of IPMC depends on the accumulation of water molecules on the mesoscopic scale, the more water molecules there are under the action of an electric field, the more pronounced the bending of IPMC will be, and the better the actuation performance will be. After up to 24 h of saturated solution immersion, ion exchange can be completed.…”
Section: Selection Of New Preparation Technologymentioning
confidence: 99%
“…Guo et al used PEDOT layer to prevent the water exchange between IPMC and the external environment and improved the working time of IPMC [116] , as shown in Figure 7E. Besides, the materials used for encapsulation of IPMC include parylene [117] , PDMS [118] , PVP [119] and liquid metal [120] .…”
Section: Increasing Wu Capacitymentioning
confidence: 99%